Meaning analyses and Dynamic Equivalance - Zilolakhon Sheraliyeva (Journal of Innovation in Education and Social Research, 2024)
Translation is an interlingual and intercultural communication, in which correspondence at the level of formal and meaningful structures does not necessarily lead to a successful communication: a secondary communication or even a communication breakdown may occur due to distinct historical-cultural contexts. Such recognition led Nida to put forward Dynamic Equivalence, which brings the receptor to the centre of the communication. The concept triggered the focus shift from the form of the message to the response of the receptor. Further, its theoretical basis went beyond applying the research results of linguistics to the practice of translation; it founded a linguistic theory of translation for researchers and provided a practical manual of translation for translators.